Da decisão discricionária: no âmbito administrativo e judicial - Feriani, Luis Arlindo (2014)
The thesis discusses how the legal issues are decided in the judicial context, but also the decisions under administrative proceedings. The primary goal is more specifically the treatment that should be given to the discretion. Start with the analysis of the concept of discretion to conclude that it can be used by the judge as a means to interpret the facts and even can get to the applicable law, however, to decide, the conclusion will be the effect that the judge can not decide with discretion. Furthermore, efforts will be made to demonstrate that the same does not occur with the public administrator. Understanding is in the sense that, despite doctrinal position exists asserting that the administrator also can not decide with discretion, it can not maintain that administrative discretion has been entirely eliminated. Indeed, as will be shown, to the administrator should be given some portion of discretion in assessing the public interest in each case. As the legislator is unable to consider all possible occurrence of the daily routine, only the administrator in contact with social reality, can decide what seems better for the community. That way, the thesis will highlight that, while it requires the court to take the best decision, and not one among many possible and acceptable, administratively, although it can not fail to consider that there was a mitigation of the discretion, it continues to exist so that it can best be served to the public interest